دراسة تحليلية للعوامل المؤثرة على ربحية شركات التأمين التكافلي في سورية - محمود, يوسف; دريباتي, يسيرة; يوسف, علي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research aims to study the Takaful insurance companies and finding the most important factors affecting the profitability of these companies in the Syrian Arab Republic during the period between 2008-2014, has been studied Takaful insurance companies operating in Syria / Aqeel-Islamic /, and to identify the most significant factors affecting the profitability was used return on assets and return on equity as dependent variables, while considered / financial leverage, company size, age of the company, liquidity, risk/ independent variables affecting the profitability of companies, Panel data were used to analyze the data and draw conclusions. It was reached through research that the financial leverage and the company's age and liquidity has a positive impact on the profitability of the Takaful insurance companies in Syria, while the risk has adversely affect. In return the company's size has not played a significant role in influencing the profitability of the Takaful insurance companies in Syria. يهدف هذا البحث إلى إيجاد أهم العوامل المؤثرة على ربحية شركات التأمين التكافلي في الجمهورية العربية السورية خلال الفترة الممتدة ما بين 2008-2014، حيث تمت دراسة شركتي التأمين التكافلي العاملة في سورية /العقيلة-الإسلامية/، والتعرف على أبرز العوامل المؤثرة على مؤشر الربحية حيث تم اعتماد العائد على الأصول والعائد على حقوق الملكية كمتغيرات تابعة، بينما اعتبر كل من /الرافعة المالية،حجم الشركة،عمر الشركة،السيولة،الخطر/ كمتغيرات مستقلة مؤثرة على ربحية الشركات. واستخدمت الدراسة بيانات بانل panel data لتحليل البيانات واستخلاص النتائج. تم التوصل من خلال البحث إلى أن الرافعة المالية وعمر الشركة والسيولة تؤثر بشكل إيجابي وطردي على ربحية شركات التأمين التكافلي في سورية، في حين أن الخطر يؤثر بشكل سلبي.بالمقابل لم يلعب حجم الشركة دوراً معنوياً في التأثير على ربحية شركات التأمين التكافلي في سورية.